THE TADPOLE OF THE MEXICAN TREE FROG CHARADRAHYLA TAENIOPUS (ANURA: HYLIDAE) - MOISES KAPLAN; PETER HEIMES (Caldasia)
The tadpole of Charadrahyla taeniopus is described. This tadpole is a typical stream-dweller with a long depressed body, oral disc completely surrounded by marginal papillae with numerous small submarginal papillae lateral to the mouth, and several rows of teeth on the posterior labium (6-7).